“Fake news” dan Pemolisian: Pendekatan Diagram Kreativitas - Sudama, I Nyoman (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
Policing and fake news have been viewed as a linear relation, particularly by the practice of conventional policing that focuses on law enforcement activities. Fake news is a negative mode in nature and must be handled in such a way that will not trigger societal disorders or influence people to engage in criminal behaviors. By utilizing the conceptual application method, this paper analyses fake news as a meme – holon-parton defined in creative practice theory. Therefore, it is part of a field that could make fake news become popular memes as there are competition in the field to gain fake news popularity which also depends upon the purpose and goals of creating them. The popularities give advantages for fake news creators in term of capital and influence agent’s habitus. Overall, the presence of fake news and its popularity affect agents in the field of social systems. This fake news (negativity) impacts the police domain to take necessary actions in the form of policing choices so fake news cycles become popular can be controlled for security and well-being purposes.